Implementation of the Free School Bus Program as Educational Support Facilities and Infrastructure at the Education and Culture Office of West Sumbawa Regency - Wijaya, Erwin; Suparman, Suparman; Anwar, Anwar (JUPE : Jurnal Pendidikan Mandala, 2023)
This research discusses free school bus implementation program as educational support facilities and infrastructure at the Education and Culture Department West Sumbawa Regency. Free school bus implementation program based on several conceptual foundations that aim to facilitate better education's access for students. This because limited public transportation and inadequate road infrastructure make it difficult for students in remote areas to access education properly. The aim of this research is to explain the implementation process of the free school bus program, analyze the impact of implementation, and the obstacles faced. The research method used is quantitative descriptive by collecting data from various related parties, such as students, parents of students, teachers and officials related to the free school bus program using questionnaires and interviews. The questionnaire contains a series of questions that related to free school bus implementation program. These questions cover relevant aspects such as student attendance, service quality, user satisfaction, and problems encountered. Meanwhile, interviews used to gain a deeper understanding of the experiences and views of users and managers regarding the implementation of the free school bus program in West Sumbawa Regency. Based on the results, it known that the importance of implementing the school bus program is because some students are sometimes absent due to unexpected transportation problems, such as damage to the family vehicle or health problems. Apart from that, students with limited mobility or families with economic limitations are reasons to implement a school bus program in West Sumbawa Regency cause several students may have limited access to private transportation. The implementation of the free school bus program in West Sumbawa Regency had a positive impact on participation and the quality of education. The implementation process of this program played an important role in increasing student accessibility to school, which in turn has an impact on increased student attendance and the quality of learning. By overcoming transportation barriers, it is easier for students to attend school regularly, increase engagement in the educational process, and minimize unplanned absences. Apart from that, this program also supports education progress by helping create a more conducive learning environment.